Formulation And Evaluation Of Biodegradable Microspheres For Controlled Release Of Glibenclamide - Yadava, Rajiv; Gaddam, Durga Prameela.; Sharma, Rohitashav; Rathore, Urmila; Shukla, Kavita; Babu, Ramenani Hari; Arora, Pooja; Patel, Jeevan; Brahma, Chandan Kumar (Journal of Neonatal Surgery, 2025)
The development of sustained-release drug delivery systems, particularly biodegradable microspheres, offers a promising approach to enhance the therapeutic efficacy and patient compliance for drugs like Glibenclamide, which traditionally requires frequent dosing due to its short elimination half-life (Rashmi R Kokardekar et al., 2015). Glibenclamide, an oral anti-hyperglycemic agent for non-insulin-dependent diabetes mellitus, can benefit significantly from controlled release formulations that overcome issues such as the "all or nothing" effect and non-uniform drug release associated with conventional extended-release single-unit dosage forms (Rashmi R Kokardekar et al., 2015). Microspheres, ranging from 1 to 1000 µm, are multi-particulate drug carrier systems designed to improve drug bioavailability and minimize side effects by providing a constant and prolonged therapeutic effect, or by targeting specific sites (Prashant Singh & Ritu M. Gilgotra, 2020). This research investigates the formulation and evaluation of biodegradable Glibenclamide microspheres, focusing on their physicochemical properties, drug entrapment efficiency, and in-vitro release kinetics. Various methods have been employed for preparing biodegradable microspheres containing Glibenclamide, primarily aiming for sustained drug release and enhanced patient adherence. For instance, Simvastatin-loaded PLGA microspheres were prepared using an oil-in-water emulsion/solvent evaporation method, demonstrating its applicability for controlled release systems (*Email: jafarzattums.ac.ir, 2016). In the context of Glibenclamide, studies have utilized emulsion-solvent evaporation with polymers like Ethyl Cellulose N100, a water-insoluble polymer known for its biocompatibility, stability, ease of fabrication, and cost-effectiveness, to achieve sustained release for up to 24 hours (Rashmi R Kokardekar et al., 2015). This method involves dissolving the drug and polymer in a suitable solvent, which is then dispersed into an encapsulating medium, allowing the solvent to evaporate and form solid microspheres (Prashant Singh & Ritu M. Gilgotra, 2020).